2012
DOI: 10.1177/1461445612457485
|View full text |Cite
|
Sign up to set email alerts
|

Compliance, resistance and incipient compliance when responding to directives

Abstract: How does a parent get a child to do something? And, indeed, how might the child avoid complying or seem to comply without actually having done so? This article uses conversation analysis to identify the interactionally preferred and dispreferred response to directives (compliance and resistance respectively). It then focuses on one alternative response option that has both verbal and embodied elements. The first part involves an embodied display of incipient compliance. That is, actions that are preparatory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 41 publications
(50 reference statements)
2
67
0
2
Order By: Relevance
“…In contrast to previous studies of directives, which have taken the social action as their point of departure (e.g., Kent, 2012b), our methodological approach mirrors that of Schegloff (1997, p. 506), who began with a series of practices for initiating repair and proceeded to "examine occasions in which they are deployed to quite different effect." By starting with grammatical imperatives rather than the social action of admonishing or directing, we aim to address Mondada's (2011, p. 19) observation that "studies focusing on directives produced by using imperative verbs are scarce, and their situated use in specific social actions remains understudied" (but see Rossi, 2012;Zinken & Ogiermann, 2013).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to previous studies of directives, which have taken the social action as their point of departure (e.g., Kent, 2012b), our methodological approach mirrors that of Schegloff (1997, p. 506), who began with a series of practices for initiating repair and proceeded to "examine occasions in which they are deployed to quite different effect." By starting with grammatical imperatives rather than the social action of admonishing or directing, we aim to address Mondada's (2011, p. 19) observation that "studies focusing on directives produced by using imperative verbs are scarce, and their situated use in specific social actions remains understudied" (but see Rossi, 2012;Zinken & Ogiermann, 2013).…”
Section: Methodsmentioning
confidence: 90%
“…In this article, we begin to disentangle imperative grammar from (some of) the many actions it is used to perform. We narrow in on a specific interactional contingency that speakers recurrently use imperative actions to manage: directing the actions of others (Craven & Potter, 2010;Goodwin, 2006;Goodwin & Cekaite, 2013;Kent, 2012b)-that is, first pair-parts that make embodied compliance conditionally relevant as a next action (Kent, 2012a). Within this class of imperative directives, we observe two basic types: (a) those that simply direct the actions of others (e.g., "pass the bread, please") and (b) those that not only prospectively direct the actions of others but also retrospectively treat the recipients as accountable for their current actions or inaction (e.g., "tell me the goddamn story").…”
mentioning
confidence: 99%
“…directives (Craven & Potter, 2010;Antaki & Kent, 2012;Kent 2012) strongly suggested that negotiations were much more one-sided. And the research that we report in this article reveals that or-formatted directives are a vehicle for a particularly loaded way of issuing warnings and threats -while appearing to be sensitive to the child's freedom of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Recipients, as well as speakers, designed their talk to display their deontic stance towards the projected course of action. When responding to parental directives, the timing and nature of a child's compliance could enable them to regain autonomy over their behaviour without openly defying the directive (Kent 2012). In other words, it was found that the struggle over deontic authority could play out in such a way as not only to identify what rights and entitlements are in play between the participants, but also what the possibilities and consequences of compliance or resistance might be.…”
Section: Requests Directives and Alternativesmentioning
confidence: 99%
“…From their interviews with 90 children aged between five and 17, McIntosh and Punch (2009) conclude that the power traditionally associated with older siblings is in fact often contested, resisted or negotiated. Likewise, Kent (2012) urges researchers to examine the specifics of each interaction rather than assume particular status hierarchies. Another factor, which may shape the 1 Exceptions include de Leon (2007), Goodwin (2017), and Hester & Hester (2010).…”
Section: Birth Order and Interactionmentioning
confidence: 99%